The Impact of Hormonal Contraceptive Use on Serotonergic Neurotransmission and Antidepressant Treatment Response: Results From the NeuroPharm 1 Study - Larsen, Søren Vinther; Ozenne, Brice; Köhler-Forsberg, Kristin; Poulsen, Asbjørn Seenithamby; Dam, Vibeke Høyrup; Svarer, Claus; Knudsen, Gitte Moos; Jørgensen, Martin Balslev; Frokjaer, Vibe Gedso (Frontiers in Endocrinology, 2022)
Background: Hormonal contraceptive (HC) use has been associated with an increased risk of developing a depressive episode. This might be related to HCs effect on the serotonergic brain system as suggested by recent cross-sectional data from our group, which show that healthy oral contraceptive (OC) users relative to non-users have lower cerebral serotonin 4 receptor (5-HT4R) levels. Here, we determine if cerebral 5-HT4R binding differs between HC non-users, OC users, and hormonal intrauterine device (HIUD) users among women with an untreated depressive episode. Also, we test if antidepressant drug treatment response and its association with pre-treatment 5-HT4R binding depends on HC status. Methods: [11C]-SB207145 Positron Emission Tomography imaging data from the NeuroPharm-NP1 Study (NCT02869035) were available from 59 depressed premenopausal women, of which 26 used OCs and 10 used HIUDs. The participants were treated with escitalopram. Treatment response was measured as the relative change in the Hamilton Depression Rating Scale 6 items (rΔHAMD6) from baseline to week eight. Latent variable models were used to evaluate the association between global 5-HT4R binding and OC and HIUD use as well as rΔHAMD6. Results: We found no evidence of a difference in global 5-HT4R binding between depressed HC users and non-users (p≥0.51). A significant crossover interaction (p=0.02) was observed between non-users and OC users in the association between baseline global 5-HT4R binding and week eight rΔHAMD6; OC users had 3-4% lower binding compared to non-users for every 10% percent less improvement in HAMD6. Within the groups, we observed a trend towards a positive association in non-users (padj=0.10) and a negative association in OC users (padj=0.07). We found no strong evidence of a difference in treatment response between the groups (p=0.13). Conclusions: We found no difference in 5-HT4R binding between HC users vs. non-users in depressed women, however, it seemed that 5-HT4R settings differed qualitatively in their relation to antidepressant drug treatment response between OC users and non-users. From this we speculate that depressed OC users constitutes a special serotonin subtype of depression, which might have implications for antidepressant drug treatment response.